PEMBERDAYAAN PEREMPUAN PESISIR MELALUI PRODUK RENGGINING KEPITING BAKAU SINGKONG DALAM RANGKA HILIRISASI AGROMARITIM - Adibrata, Sudirman; Syaputra, Denny; Wahidin, La ode (Jurnal Abdi Insani, 2025)
The welfare of the fish farming group of Pagarawan Village, Bangka Regency, and their wives, can be increased by utilizing natural resources maximally. Pagarawan Village situated in Baturusa Watershed Selindung Sub-Watershed, has an extensive mangrove ecosystem which feature mangrove crab (Scylla sp.) opportunity. This program is a part of efforts to strengthen the capacity of coastal women in the downstream processing of agromaritime products such as mangrove crab and renggining that is made of cassava. Activity Start Date End Date from June to July 2025 at the Kulong Kelat Sukses Fish Farming Group (Pokdakan KKS) in Pagarawan Village, Sub-District of Merawang, District of Bangka, Province of Kepulauan Bangka Belitung. The method is participatory and applied based on strengthening the women members of fish farmers’ group with local potential as an active community of women involved in household economic activities. The result of the activity showed that the training on crab and cassava based renggining processing was comprehendible and managed to improve the technical capabilities of its members in the production process of crab and cassava based renggining, the packing of renggining, as well as the selling of the product. This empowerment has translated into a higher familial income and higher status of women in household financial matters. Beyond producing economic benefits, the use of mangrove crabs has an ecological advantage by controlling the total exploitation rate of small and large mangrove crabs in the mangrove ecosystem. It also encourages an entrepreneurial mindset and solidarity among members which could evolve into a women’s economic institution. The programʼs success requires strong community participation, sustainable technology and intensive academic training. This agromaritime downstream-based empowerment model has proven to be effective, sustainable, and replicable in other coastal areas with similar characteristics, provided it is supported by cross-sector collaboration and village empowerment programs. Overall, the program strengthens the local economy, enhances the role of women, and supports the conservation of coastal resources.